Extreme wave interaction with a floating oil rig: prediction using SPH. (23rd July 2009) - Cleary, Paul W.; Rudman, Murray
Two-way coupling of the effects of wave impact on moored offshore structures is a challenging problem, especially in the case of large amplitude motions produced by extreme wave impact. We explore fully-3D wave impact behaviour on a semi-submersible platform using Smoothed Particle Hydrodynamics (SPH). Wave impact and propagation around and through the structure is complex and induces non-trivial motion. Large waves can impact the underside of the production deck or the upper superstructure. Such impacts can induce dangerous motions, threaten the structural integrity of the platform and create significant risk to people and equipment. These issues are investigated for different mooring configurations and a range of wave heights.